"A Noble Experiment in Human Values": The Children's Television Series Vegetable Soup and Its Initiative to Change the Environment for Racism in 1970s America. Issue 3 (3rd July 2018) - Reznick, Jeffrey S.
Abstract: : This article explores the creation, production, and reception of the unique, popular, and publicly-funded mid-1970s children's television series Vegetable Soup, arguing that it constitutes a specific and intriguing chapter in the history of efforts in the United States to change "the environment for racism."